THE MAGIC OF DARK TOURISM - Erika KULCSÁR; Rozalina Zsófia SIMON (Management & Marketing, 2015)
The dark tourism is a form of tourism that is not unanimously accepted by the whole society, but in spite of this fact, the practitioners of dark tourism is a viable segment. Indeed the concept that defines dark tourism is none other than death, and perhaps this is why it will always be a segment that will not be attracted by this form of tourism. Many questions about dark tourism arise. Among them: (1) is dark tourism an area of science attractive for researches? (2) which is the typology of dark tourism? (3) what are the motivating factors that determine practicing dark tourism? This paper provides a detailed analysis of publication behaviour in the field of dark tourism. The article also includes the main results obtained by achieving a quantitative marketing research among students of Sfantu Gheorghe University Extension in order to know their opinion, attitude towards dark tourism.